The use of carbon taxes and charges in climate policy - Michał Ptak (Economic and Environmental Studies (E&ES), 2013)
The main aim of this article is to discusses theoretical issues regarding the use of carbon taxes in climate policy. The issues include inter alia: the definition of carbon and CO2 taxes, the objectives of these instruments and the tax design (the point at which the tax is levied, tax rates, tax exemptions). Attention is paid to the advantages and disadvantages of carbon taxes over another climate policy instrument which is the tradable emissions allowances system. Carbon or CO2 taxes (charges) have been introduced in a number of European countries. The article presents experience gained by those countries in the field of carbon taxation and results of ex post studies evaluating environmental impact of carbon taxes.
Keywords: 330; climate change; carbon taxes; CO2 taxes